Disproportionate minority contact and racism in the US : how we failed children of color - Ketchum, Paul R., 1962-; Peck, B. Mitchell (Bristol, UK : Bristol University Press, 2022)
Drawing on original data, this book addresses the issue of color-blind racism through an examination of the circular logic used by the juvenile justice system to criminalize non-White youth. It calls for a need to understand racial inequality in the justice system from a structural perspective rather than simply at the level of individual bias.
Title from publisher's bibliographic system (viewed on 15 Sep 2022).
Keywords: Juvenile delinquents -- United States; Minority youth -- United States; Crime and race -- United States; Discrimination in juvenile justice administration -- United States; Juvenile justice, Administration of -- United States